Human AlkB homologue 5 is a nuclear 2-oxoglutarate dependent oxygenase and a direct target of hypoxia-inducible factor 1α (HIF-1α) - Thalhammer, Armin; Bencokova, Zuzana; Poole, Rachel; Loenarz, Christoph; Adam, Julie; O'Flaherty, Linda; Schödel, Johannes; Mole, David; Giaslakiotis, Konstantinos; Schofield, Christopher J.; Hammond, Ester M.; Ratcliffe, Peter John; et al. (PLoS ONE, 2011)
Human 2-oxoglutarate oxygenases catalyse a range of biological oxidations including the demethylation of histone and nucleic acid substrates and the hydroxylation of proteins and small molecules. Some of these processes are centrally involved in regulation of cellular responses to hypoxia. The ALKBH proteins are a sub-family of 2OG oxygenases that are defined by homology to the Escherichia coli DNA-methylation repair enzyme AlkB. Here we report evidence that ALKBH5 is probably unique amongst the ALKBH genes in being a direct transcriptional target of hypoxia inducible factor-1 (HIF-1) and is induced by hypoxia in a range of cell types. We show that purified recombinant ALKBH5 is a bona fide 2OG oxygenase that catalyses the decarboxylation of 2OG but appears to have different prime substrate requirements from those so far defined for other ALKBH family members. Our findings define a new class of HIF-transcriptional target gene and suggest that ALKBH5 may have a role in the regulation of cellular responses to hypoxia. © 2011 Thallhammer et al.
CRIS-Team Scopus Importer:2024-05-13